Long-term experience in treatment of acute promyelocytic leukemia in Mexican children in a tertiary care hospital - Murillo-Maldonado, Marco Antonio; Galván, Paulina González; Ortega, Israel Parra; Morales, Félix Gaytán; Villegas, Luis Juárez; Acosta, Elisa Dorantes (Frontiers in Oncology, 2023)
Introduction: Acute promyelocytic leukemia (APL) is a rare myeloid leukemia subtype affecting adult and pediatric populations. APL constitutes 15-20% of all childhood AML in Latin America, compared to 7% in the non-Latino population. This leukemia has unique characteristics, such as its association with chromosomal translocations involving the retinoid acid receptor α (RARA) gene on chromosome 17. In addition, APL is also distinct from other AML subtypes due to its response to all-trans-retinoic acid (ATRA), which induces terminal granulocytic differentiation of blasts. Overall 5-year survival rates are generally reported to be greater than 80%. Material and methods: A study was conducted from January 2008 to December 2022 applying the IC-APL 2006 treatment protocol. This case series reports the clinical results of 22 children with APL. In all cases, the diagnosis was made by bone marrow aspiration and evaluation of the t(15:17) or t(11:17) transcripts. Results: We identified 22 patients with APL, of whom 10 were female and 12 were male. Twelve patients debuted with coagulation abnormalities. The doses of anthracyclines varied according to the risk, with an average of 496.8 mgm 2 . The cardiological assessment was performed before and after chemotherapy, finding 2/22 patients with moderate sisto-diastolic dysfunction and one with mild pulmonary insufficiency at the end of treatment. There were 6/22 patients with complications related to ATRA treatment, the most frequent being pseudotumor cerebri. All complications were transitory and treated immediately without complications. In this series of cases, an overall survival of 90.6% and a relapse-free survival of 90.6% were recorded. The follow-up mean was 9.1±3.8 years. Conclusions: APL is a highly curable disease when combined with ATRA and anthracyclines. In this series of cases, good long-term results were observed with the IC-APL 2006 protocol. However, in Latin America, the availability of drugs such as arsenic trioxide as the first line of treatment is an unresolved challenge.